Theoretical Calculations of the Temperature and Impurity Dependence of the Lattice Thermal Conductivity of the ZnSnAs2 Semiconductor Compound - Saeed, Salah R. (Sulaimani Journal for Pure and Applied Sciences, 2003)
The Callaway models are used to calculate lattice thermal conductivity for ZnSnAs2 Semiconductor in the temperature range (2-300) K The dependence of lattice thermal conductivity on temperature and impurity concentration as well as the strength of scattering are discussed, The maximum thermal conductivity for elven samples investigated are appears at the temperature 21K. is 3.54 W/cm.K,This reduces to 0.093 W/cm.K for impurity concentrations from 0.21x102° cm-3 to 10023 cm-3. The scattering strength is also investigated and found to be equal to -0.7203.
Keywords: ZnSnAs2 Semiconductor; Lattice Thermal Conductivity; Carrier Concentration relaxation time